Efficacy of epicardial implantation of acellular chitosan hydrogels in ischemic and nonischemic heart failure: impact of the acetylation degree of chitosan. (1st January 2021) - Domengé, Orianne; Ragot, Hélène; Deloux, Robin; Crépet, Agnès; Revet, Gaëlle; Boitard, Solène Emmanuelle; Simon, Alexandre; Mougenot, Nathalie; David, Laurent; Delair, Thierry; Montembault, Alexandra; Agbulut, Onnik
Abstract: This work explores the epicardial implantation of acellular chitosan hydrogels in two murine models of cardiomyopathy, focusing on their potential to restore the functional capacity of the heart. Different chitosan hydrogels were generated using polymers of four degrees of acetylation, ranging from 2.5% to 38%, because the degree of acetylation affects their degradation and biological activity. The hydrogels were adjusted to a 3% final polymer concentration. After complete macromolecular characterization of the chitosans and study of the mechanical properties of the resulting hydrogels, they were sutured onto the surface of the myocardium, first in rat after four-weeks of coronary ligation (n=58) then in mice with cardiomyopathy induced by a cardiac-specific invalidation of serum response factor (n=20). The implantation of the hydrogels was associated with a reversion of cardiac function loss with maximal effects for the acetylation degree of 24%. The extent of fibrosis, the cardiomyocyte length-to-width ratio, as well as the genes involved in fibrosis and stress were repressed after implantation. Our study demonstrated the beneficial effects of chitosan hydrogels, particularly with polymers of high degrees of acetylation, on cardiac remodeling in two cardiomyopathy models. Our findings indicate they have great potential as a reliable therapeutic approach to heart failure. Graphical abstract: Image, graphical abstract